Belajar Statistika: Mengapa dan Bagaimana? - Maria Ulpah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
Students usually tend to view statistics subject negatively. These studentsâ€™ attitudes toward statistics and their implications for statistics instruction have long been a commonly shared interest among statistics educators. It causes educators modify their teaching according to suggestions from the research literature, and to use assessment to determine if their teaching is effective and if students are developing statistical underÂstanding and competence. Besides that, positive thinking should be built when learning process is running. Nowadays, statistics has recently applied in education, technology, politics, business, etc.